2016
DOI: 10.1002/nml.21231
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effectiveness of Fundraiser Job Titles in Charitable Bequest and Complex Gift Planning

Abstract: Traditional fundraiser job titles are often institution centered, focusing on the benefits of fundraising as “institutional advancement” or “institutional development.” Such institution‐centered job titles may not be as effective with donors given the modern shift toward donor‐centered philanthropy. Alternative job titles can be gift centered (for example, “major gifts”) or donor centered (for example, “donor advising”). A survey of 3,188 respondents tested sixty‐three job titles in four charitable scenarios: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…For practitioners, whether fundraisers, nonprofit leadership, or funders, managing the interests of different stakeholders is often challenging. Recent years have emphasized the donors' interests in fundraising practice (James III, 2016). Clients' interests may or may not be in tension with those of donors and the organization itself.…”
Section: Notes For Practicementioning
confidence: 99%
“…For practitioners, whether fundraisers, nonprofit leadership, or funders, managing the interests of different stakeholders is often challenging. Recent years have emphasized the donors' interests in fundraising practice (James III, 2016). Clients' interests may or may not be in tension with those of donors and the organization itself.…”
Section: Notes For Practicementioning
confidence: 99%
“…Furthermore, the findings here about the use of avoiding strategies can be usefully combined with James III's () recent research testing the varying financial success of different fundraiser titles in helping fundraisers make contact with potential donors. The most common form of avoiding strategies found in the current project involved avoiding using the word “fundraiser” to describe their jobs.…”
Section: Discussionmentioning
confidence: 81%
“…Despite these concerning conditions, systematic research on fundraisers is scarce, with the most comprehensive studies having been conducted over 20 years ago (Brittingham & Pezzullo, ; Kelly, , ). Recent fundraising research has focused on donors (e.g., Croson, Handy, & Shang, ) and on increasing the success of those engaged in fundraising (e.g., James III, ), rather than on understanding fundraisers' career choices and identity constructions. In the philanthropic field more broadly, Stewart () recently investigated how nonprofit executives experience turnover processes, but her research did not focus on the fundraising elements of such turnover.…”
Section: Introductionmentioning
confidence: 99%
“…For example, James (), in a test of alternative phrasings describing a charitable estate gift found that respondents were the least interested in making a gift when it was described using the formal term “bequest gift to charity,” but much more interested if the description used the less formal phrase “gift to charity in your will” (p. 1005). Separately, donors were much less willing to contact a fundraiser for help in making a complex charitable gift if the fundraiser's job title used industry insider language like “advancement” or “development,” than if it used simple descriptive language, like “donor advising” (James, , p. 165). Together with the current results, this suggests that, although likely requiring a determined effort for those who are technically proficient in complex charitable planning, intentionally shifting to language that is more informal will result in greater interest in such gifts.…”
Section: Discussionmentioning
confidence: 99%